Frequency of Urinary Tract Infections in Patients with Type-II Diabetes Mellitus - Muhammad Naveed Iqbal, Kiran Khan, Aftab Hussain Abro, Ata Ur Rehman, Ali Nawaz Bijarani, Naveed Nayyer (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes mellitus has several adverse effects on the genitourinary system. Individuals with both type 1 and type 2 diabetes are at an increased risk of developing urinary tract infections. Considering the increasing incidence of UTIs over time, current study aimed to evaluate the frequency of urinary tract infections in patients with type-II diabetes mellitus. Methods: A descriptive cross-sectional study was conducted in the Department of Medicine, Shahida Islam Medical and Dental College, Lodhran. A detailed medical history was obtained from each participant, followed by a thorough physical examination and routine laboratory investigations. Blood glucose levels and glycated hemoglobin (HbA1c) were measured to assess glycemic control. Evaluation for urinary tract infection included urine microscopy, with leukocyte quantification performed using glass slide examination. Data was analysed using SPSS version 22. The chi-square test was applied to find out the association between glycaemic status and the presence of UTI, and a p-value of ≤ 0.05 was considered statistically significant. Results: The mean age of the study participants was 55.4 ±8.2 years. Majority of study participants (64%) were female as compared to their male counterpart. Mean duration of diabetes was 9.75 ± 3.8 years while past history of UTI was positive among 32.6% participants. Looking over the glycemic status, the frequency of UTI was positive in 85.6% poorly controlled diabetic patients and 14.4% in good glycemic controlled patients and the results were significant (p-value ≤0.05). The most commonly found pathogen was E.coli followed by proteus, staphylococcus aureus, pseudomonas aeruginosa, klebsiella, Enterobacteriaceae and clostridium albicans with frequency of 65%, 13%, 12%, 5%, 3%, 2% and 2% respectively. Conclusion: The prevalence of urinary tract infection is higher among patients with sustained hyperglycemia or inadequate glycemic control, and Escherichia coli remains the most common causative organism in diabetic patients. Keywords: Diabetes mellitus, Urinary tract infection, E.coli.